Indonesian Textbooks Oriented on Social Integration and 21st Century Skills in Higher Education: Validity, Practicality, and Effectiveness - Susrawan, I Nyoman Adi; Suandi, Nengah; Sudiana, I Nyoman; Dewantara, I Putu Mas (International Journal of Language Education, 2024)
This research problem is how to overcome the need for Indonesian textbooks that integrate social and 21st century skills. This research aims to develop valid, practical, and effective textbooks to improve students' Indonesian understanding. The research design uses Research and Development (R&D) methods. The research was conducted at the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Mahasaraswati University, Denpasar. Data was collected through documentation techniques, Focus Group Discussions, questionnaires, and test administration. The instrument involves documentation sheets, validation, questionnaires, and self-evaluation. Data analysis focuses on the validity, practicality, and effectiveness of textbooks with parameters of (1) level of validity, (2) level of practicality, and (3) level of effectiveness. The results suggest the need for continuous development of appropriate and effective textbooks to meet students' needs and educational development. Research reveals that the textbook meets the criteria of validity, practicality, and effectiveness. The results suggest the need for continuous development of appropriate and effective textbooks to meet students' needs and educational development.